Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan Bagi Para Pelaku Umkm Budidaya Ikan Nila Desa Tantan Kecamatan Sekernan Kabupaten Muaro Jambi - Bakri Bakri; As’ad As’ad; Eja Armaz Hardi (Institut Nalanda, 2023)
This research was conducted with the aim of knowing and analyzing financial knowledge, financial attitudes and personality towards financial management behavior for business, micro, small and medium enterprises (MSMEs) in tilapia cultivation in Tantan Village, Sekernan District, Muaro Jambi Regency. and using the method of analysis with the coefficient of determination, the researchers used 27 people as resource persons to find out the results of the study. In partial research, the results show that financial knowledge, financial attitudes and personality have a positive effect on financial management behavior. Simultaneously, it shows that the variables of financial knowledge, financial attitude and personality have a positive influence on financial management behavior towards business actors. In the calculation of the coefficient of determination, it shows that the variables have an influence of 68.4% and 31.6% are influenced by variables outside this study.